NATIONAL CONTRADICTIONS IN KAZAKHSTAN SOCIETY AND WAYS OF THEIR SOLUTION - Absattarov, R.B.; Seisen, N.B.; Absattarov, G.R.; Nabiyev, V.G. (Scientific Journal of Pedagogy and Economics, 2020)
The article focuses on the politological aspects of national contradictions in Kazakhstani society and ways to solve them, which have not yet been studied in socio-political science. The paper emphasizes that the restructuring, updating, modernization of national relations is contradictory in its way, and practice cannot but take this into account. Herewith, it should be said that the peoples of Kazakhstan can resolve national contradictions based on a commonality of the fundamental interests of all nationalities and the implementation of the correct scientific national policy. Of course, these contradictions are not resolved by themselves, their overcoming requires certain efforts, tension, and sometimes struggle. The strength of the commonwealth of the peoples of Kazakhstan lies in the fact that the democratic system and the right scientific national policy give all the opportunities to overcome these contradictions, allow society to resolve them promptly, avoiding home-base mistrust, envy, and any nationalistic, chauvinistic, extremist, tribalistic feelings in general. The study shows that the update, reformation, modernization of Kazakhstani society revealed national contradictions in the main areas of the country's life: economic, socio-political, and spiritual. We think that the main ones among them are the contradictions between the principle of equal rights of large and small-numbered nations, and the unequal opportunities to meet their needs, between national and international in the trends of development and rapprochement of peoples; between the growth of national identity and the deepening of internationalization; between countrywide and national patriotism, etc. These and other national contradictions and problems must be resolved on a truly democratic basis, in the context of the struggle for socio-economic progress. They can be successfully resolved only based on science and the paths of the law, preserving the integrity of the country, seeking consent and mutually acceptable solutions, respecting the equal rights and freedom of people and nations. At the same time, the article focuses on discussing issues.